(untitled) (Research, Society and Development, 2022)
Antiphospholipid Antibody Syndrome (APS), an autoimmune disease characterized by the occurrence of thrombotic events in any vascular bed and gestational events. This study aims to identify the main obstetric complications in pregnant women with APS, based on the analysis of scientific productions. This is an integrative literature review, with a qualitative approach, using the DeCS: pregnancy, abortion, thrombosis. The Medical Literature Analysis and Retrievel System Online (MEDLINE) and Latin American and Caribbean Literature on Health Sciences (LILACS) databases were used through the Virtual Health Library (BVS), in October 2021, for through the Descriptors in Health Sciences (DeCS): “pregnancy”, “abortion” and “thrombosis”, using the Boolean term AND in the searches. 249 articles were found, and through the inclusion and exclusion criteria, 4 articles were selected for analysis. The results showed that FAS is treated as an immunodeficiency and among the main complications in pregnancy are: fetal death, recurrent miscarriages in the first months due to placental insufficiency, deep vein thrombosis (DVT) in the lower limbs, and pulmonary thromboembolism (PTE). It can result in maternal death. For this, it is extremely important that any signs of bleeding and miscarriage that occur, the pregnant woman should seek specialized medical assistance to manage the problem. Primary care has the role of instructing these women to carry out laboratory tests, as well as offering prenatal care and quality obstetric follow-up.